The role of intravascular imaging in chronic total occlusion percutaneous coronary intervention - Xenogiannis, Iosif; Pavlidis, Antonis N.; Kaier, Thomas E.; Rigopoulos, Angelos G.; Karamasis, Grigoris V.; Triantafyllis, Andreas S.; Vardas, Panos; Brilakis, Emmanouil S.; Kalogeropoulos, Andreas S. (Frontiers in Cardiovascular Medicine, 2023)
Chronic total occlusions (CTOs) represent the most complex subset of coronary artery disease and therefore careful planning of CTO percutaneous coronary recanalization (PCI) strategy is of paramount importance aiming to achieve procedural success, improve patient's safety and post CTO PCI outcomes. Intravascular imaging has an essential role in facilitating CTO PCΙ. First, intravascular ultrasound (IVUS), due to its higher penetration depth compared to optical coherence tomography (OCT), and the additional capacity of real-time imaging without need for contrast injection is considered the preferred imaging modality for CTO PCI. IVUS can be used to resolve proximal cap ambiguity, facilitate wire re-entry when dissection and re-entry strategies are applied and most importantly to guide stent deployment and optimization post implantation.The role of OCT during CTO PCI is currently limited to stent sizing and optimization, however, due to its high spatial resolution, OCT is ideal for detecting stent edge dissections and strut malapposition. In this review, we describe the use of intravascular imaging for lesion crossing, stent sizing and optimization during CTO PCI and summarize the findings of the major studies in this field.